The Impact of Heavy Metals on Human Health: A Biochemical Perspective - Honyar Ahmad Xorshed Hamajan,; Mohannad Kareem Kadhum Husain,; Tariq Hussein Mudahay Mosharf,; Rusul Raad Hussein Alwan,; Zainab Maaen Ibrahim Hammadi, (American Journal of Biomedicine and Pharmacy, 2025)
Heavy metals (HMs) have become a major environmental issue because contamination of the ambient environment with HMs and other pollutants is continuously increasing due to the increasing progress in industrialization, urbanization and agricultural practices, which brings serious environmental threat to human health and ecosystem. Anthropogenic activities include mining, smelting, oil refining, landfill sites, the use of fossil fuels, industrial effluents, application of fertilizers, pesticides, herbicides, waste from chemical factories, and automotive, as well as the use of unlicensed land and groundwater. Accumulation of one or more HMs in an ecosystem, far beyond natural threshold limits, causes environmental pollution; this is of significance primarily because it leads to the degradation of air, water, and soil quality. With growing population, urbanization, and industrialization, increased undesirable exposure of human populations to HMs has been reported. Major industries contributing HMs pollution include mining, steel production, sludge from sewage treatment plants, oil refining, electroplating, fertilizer manufacturing, battery manufacturing, textile dyeing and finishing, wood preservation, leather industries, and glass manufacturing. Mercury (Hg), followed by arsenic (As), lead (Pb), chrome (Cr), and cadmium (Cd), was reported to be the most prevalent HMs causing toxicity in human biological systems today. These toxicants are widespread in air, drinking water, food, and soil. Non-essential HMs are toxic in extremely low concentrations and are shown to induce various deleterious alterations in tissues and organ systems. Poisonings of very broad spectrum can be acute (usually high exposure over a short period of time) or chronic (low exposure over an extended period of time), resulting in more subtle, long-term health effects. There may also be regional differences in types of poisoning, with endemic exposure from natural occurrences; these high exposures are often more easily quantifiable, even with ecological or soil data, and these models of exposure may also be used to predict health effects in similar populations quantitatively. In acute poisonings, HMs may cause direct toxicity in the tissues with extensive tissue damage.